Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

It needs to fulfill following condition for all positive $x,y ∈ ℝ$: $$f(x)+f(y)+2xyf(xy)=\frac{f(xy)}{f(x+y)}$$

any ideas?

share|improve this question
Based on the answers below, I guess the real question is: does anything else work? –  Semiclassical Jul 21 '14 at 1:51

3 Answers 3

up vote 14 down vote accepted

I am sorry. Try as I might, I can't rule out all possibility. However, I managed to obtain a partial result: if we further assume that the function is continuous, then there is only 1 solution. This is because I can prove that there is only 1 possible solution for rational number. As for non-continuous solution, I have a good idea on how to extend uniqueness to Euclidean field, a vague hint on how to extend uniqueness to algebraic field, but completely no clues on transcendental numbers. In fact, I suspect that there might not be unique solution once you extend the issue to transcendental number, but I have not been able to find an example of such.

Set $x=y=1$ give us $4f(1)=\frac{f(1)}{f(2)}$ so $f(2)=\frac{1}{4}$.

Set $x=y=2$ give us $2f(2)+8f(4)=\frac{f(4)}{f(4)}=1$ show that $f(4)=\frac{1}{16}$.

Set $x=1,y=2$ give us $f(1)+5f(2)=\frac{f(2)}{f(3)}$ hence $f(1)+\frac{5}{4}=\frac{1}{4f(3)}$. While set $x=1,y=3$ give us $f(1)+7f(3)=\frac{f(3)}{f(4)}$ hence $f(1)+7f(3)=16f(3)$ hence $f(1)=9f(3)$. Plug back give us $9f(3)+\frac{5}{4}=\frac{1}{4f(3)}$ which give $36(f(3))^{2}+5f(3)-1=0$ so $f(3)=\frac{-5\pm 13}{72}=\frac{1}{9},-\frac{1}{4}$. The corresponding value for $f(1)$ is $1,-\frac{9}{4}$.

Set $x=1,y=n$ for any positive integer $n$ give $f(1)+(2n+1)f(n)=\frac{f(n)}{f(n+1)}$ so $f(n+1)=\frac{f(n)}{f(1)+(2n+1)f(n)}$, which for fixed $f(1)$, determine the sequence $f(n)$.

Consider case $f(1)=-\frac{9}{4}$. We continue the sequence to find $f(5)=-\frac{1}{27},f(6)=\frac{4}{287}$

Set $x=2,y=3$ give us $f(2)+f(3)+12f(6)=\frac{f(6)}{f(5)}$. Plug in the above value give $\frac{1}{4}-\frac{1}{4}+12\frac{4}{287}=\frac{(\frac{4}{287})}{(-\frac{1}{27})}$ hence $\frac{48}{287}=-\frac{108}{287}$ contradiction. Hence $f(1)=1$ and $f(3)=\frac{1}{9}$.

Set $x=1$ and let $y$ be arbitrary we get $f(1)+f(y)+2yf(y)=\frac{f(y)}{f(n+y)}$ so $1+(2y+1)f(y)=\frac{f(y)}{f(y+1)}$ so $f(y+1)=\frac{f(y)}{1+(2y+1)f(y)}$.

Now a simple result make things easier: $\frac{(\frac{z}{1+az})}{1+b(\frac{z}{1+az})}=\frac{z}{1+(a+b)z}$. This leads by induction to $f(y+n)=\frac{f(y)}{1+f(y)\sum\limits_{k=0}^{n-1}(2(y+k)+1)}=\frac{f(y)}{1+(2y+n)nf(y)}$ (this formula will be used repeatedly, so remember this). In particular, plug in $y=1$ give us the formula $f(n)=f(1+(n-1))=\frac{1}{1+(2+n-1)(n-1)}=\frac{1}{n^{2}}$.

Take $x=n,y=\frac{1}{n}$ we get $\frac{1}{n^{2}}+f(\frac{1}{n})+2=\frac{1}{f(n+\frac{1}{n})}=\frac{1+(\frac{2}{n}+n)nf(\frac{1}{n})}{f(\frac{1}{n})}=\frac{1}{f(\frac{1}{n})}+2+n^{2}$ so $f(\frac{1}{n})-\frac{1}{f(\frac{1}{n})}=n^{2}-\frac{1}{n^{2}}$ which have only solution $f(\frac{1}{n})=n^{2}$ or $f(\frac{1}{n})=-\frac{1}{n^{2}}$

Take $x=2n,y=\frac{1}{n}$ we get $\frac{1}{4n^{2}}+f(\frac{1}{n})+1=\frac{1}{4f(2n+\frac{1}{n})}=\frac{1}{4}\frac{1+(\frac{2}{n}+2n)2nf(\frac{1}{n})}{f(\frac{1}{n})}=\frac{1}{4f(\frac{1}{n})}+1+n^{2}$ so $f(\frac{1}{n})-\frac{1}{4f(\frac{1}{n})}=n^{2}-\frac{1}{4n^{2}}$ which once again have only solution $f(\frac{1}{n})=n^{2}$ or $f(\frac{1}{n})=-\frac{1}{4n^{2}}$

Combine the above 2 results we get $f(\frac{1}{n})=n^{2}$. In other word, when $x=\frac{1}{n}$ we have $f(x)=\frac{1}{x^{2}}$.

Apply the formula with $y=\frac{1}{k}$ we get $f(n+\frac{1}{k})=\frac{f(\frac{1}{k})}{1+(\frac{2}{k}+n)nf(\frac{1}{k})}=\frac{k^{2}}{1+(\frac{2}{k}+n)nk^{2}}=\frac{k^{2}}{1+2nk+(nk)^{2}}=\frac{k^{2}}{(nk+1)^{2}}=\frac{1}{(n+\frac{1}{k})^{2}}$. Thus for $x$ of the form $n+\frac{1}{k}$ we get $f(x)=\frac{1}{x^{2}}$.

Now to find arbitrary $f(\frac{p}{q})$. Set $x=p,y=\frac{1}{q}$. We get $f(p)+f(\frac{1}{q})+2\frac{p}{q}f(\frac{p}{q})=\frac{f(\frac{p}{q})}{f(p+\frac{1}{q})}$ hence $\frac{1}{p^{2}}+q^{2}+2\frac{p}{q}f(\frac{p}{q})=(p+\frac{1}{q})^{2}f(\frac{p}{q})$ so $\frac{1}{p^{2}}+q^{2}=(p^{2}+\frac{1}{q^{2}})f(\frac{p}{q})$ so $f(\frac{p}{q})=\frac{\frac{1}{p^{2}}+q^{2}}{p^{2}+\frac{1}{q^{2}}}=(\frac{q}{p})^{2}$.

Hence for $x$ rational then $f(x)=\frac{1}{x^{2}}$.

Now if we assume that the function is continuous the only possibility is that $f(x)=\frac{1}{x^{2}}$ everywhere. Then for any $x,y$ we have $f(x)+f(y)+2xyf(xy)=\frac{1}{x^{2}}+\frac{1}{y^{2}}+2xy\frac{1}{x^{2}y^{2}}=\frac{x^{2}+y^{2}+2xy}{x^{2}y^{2}}=\frac{(x+y)^{2}}{(xy)^{2}}=\frac{f(xy)}{f(x+y)}$. Thus this is indeed a solution.

Hence the only continuous solution is $f(x)=\frac{1}{x^{2}}$.

share|improve this answer

$f(x)=\frac{1}{x^2}$ is a solution.

I came up with this by setting $x=y=1$ and finding $f(2)=\frac{1}{4}$.

Towards a proof of uniqueness:

It is trivial to show that

$$ f(x+1) = \frac{1}{1+2x+\frac{1}{f(x)}} $$

from which it follows that

\begin{align} f(x)&>\frac{1}{x^2} \Rightarrow f(x+1)>\frac{1}{(x+1)^2} \\ f(x)&<\frac{1}{x^2} \Rightarrow f(x+1)<\frac{1}{(x+1)^2} \end{align}

I'm so close I can taste it.

share|improve this answer
wow - that's astonishing! thanks –  Silenttiffy Jul 21 '14 at 1:31
This answer is undefined for $x=0$, contradict the requirement that the equality work for all $x,y\in\mathbb{R}$. –  Gina Jul 21 '14 at 1:56
@Gina "for all positive [..]" –  Silenttiffy Jul 21 '14 at 2:00
@Levix: oh right sorry. –  Gina Jul 21 '14 at 2:02
When it come to proving uniqueness, the main difficulty seems to be transcendental number: sure you might have the above equality, but 1 equality is easily satisfied, and there does not seems to be anyway to obtain any more to cause further restriction, as the number is transcendental. –  Gina Jul 21 '14 at 14:49

Set $h(x) = 1/f(x)$ and assume $f(xy) = f(x)f(y)$, then we see that

$$h(x) + h(y) + 2xy = h(x+y)$$

Thus $h(x) = x^2$ is a solution.

share|improve this answer
oops, ozo posted this also. I guess posting another approach should be ok. –  Knoothe Jul 21 '14 at 1:43
-1 I don't think you can "assume $f(xy) = f(x) f(y)$", but otherwise this is nice. –  Calvin Lin Jul 21 '14 at 3:34
@CalvinLin It's a guess that produces a valid solution. –  Casey Chu Jul 21 '14 at 4:05

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.